The textual basis of English translations of the Hebrew Bible - Daley, S. C. (Supplements to the textual history of the Bible, 2019)
Front Matter -- Copyright Page /S.C. Daley -- Dedication /S.C. Daley -- Motto /S.C. Daley -- Motto /S.C. Daley -- Foreword /S.C. Daley -- Preface /S.C. Daley -- Acknowledgements /S.C. Daley -- Abbreviations and Sigla /S.C. Daley -- Introduction /S.C. Daley -- Methodology /S.C. Daley -- Analysis of Sample Chapters /S.C. Daley -- Para-textual Elements of the Masoretic Text /S.C. Daley -- Conjectural Emendation /S.C. Daley -- Influence from the Qumran Scrolls /S.C. Daley -- Revision Lines within the English Translations /S.C. Daley -- Results: The Textual Basis of English Translations /S.C. Daley -- Implications for Future Translations /S.C. Daley -- Conclusions /S.C. Daley -- Back Matter -- Addendum /S.C. Daley -- Bibliography /S.C. Daley -- Index of Textual Problems Analyzed /S.C. Daley.